Transformasi Pembelajaran Pendidikan Pancasila Berbasis Outcome-Based Education melalui untuk Penguatan Kompetensi Mahasiswa Fakultas Ilmu Sosial dan Hukum - Apit Dulyapit; Indah Wardatussa'idah; Laely Farokhah; Fizar Indrawijaya (CV. SINAR HOWUHOWU, 2026)
Pancasila Education courses in higher education face a significant challenge in shifting from content-oriented instruction toward outcome-based learning that is relevant to twenty-first century student needs, particularly within the Faculty of Social Sciences and Law, which demands critical reasoning, legal literacy, and social sensitivity. This article aims to conceptually examine how the Outcome-Based Education (OBE) approach can be integrated with an online Project-Based Learning (PjBL) model in Pancasila Education courses, and to analyze its contribution to strengthening student competencies. This study employs a literature review method by examining recent research findings and higher education policies. The review indicates that OBE-based online PjBL transformation encourages a shift in the lecturer's role from information transmitter to project facilitator, increases students' active engagement in producing authentic learning outputs, and strengthens learning outcomes in the form of national character, critical thinking, collaboration, and digital literacy. However, implementation still faces challenges such as digital literacy gaps, the workload of designing project-based assessments, and the need for adequate technological infrastructure. This article recommends formulating measurable graduate learning outcomes, designing contextual projects grounded in current national issues, and strengthening online learning governance to optimize the transformation of Pancasila Education learning in the Faculty of Social Sciences and Law.